2010
DOI: 10.3758/s13421-010-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and forensic implications of developmental studies of the DRM illusion

Abstract: In the study of false memory, developmental research on the Deese-Roediger-McDermott (DRM) illusion has played a pivotal role in theory evaluation and forensic application. The extensive developmental DRM literature (55 experiments published in English-language journals) provided the first clear evidence that false memories can increase dramatically from early childhood onward, whereas traditional ideas about cognitive development predict steady declines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 101 publications
(147 reference statements)
4
62
0
1
Order By: Relevance
“…However, evidence is accumulating that age, by itself, cannot be used to predict false memory propensity (Brainerd, Reyna, & Zember, 2011;Otgaar et al, 2016). Instead, our research suggests that other factors should be taken into account when, for example, legal professionals (e.g., police) want to assess a witness' vulnerability to false memories.…”
Section: Discussionmentioning
confidence: 87%
“…However, evidence is accumulating that age, by itself, cannot be used to predict false memory propensity (Brainerd, Reyna, & Zember, 2011;Otgaar et al, 2016). Instead, our research suggests that other factors should be taken into account when, for example, legal professionals (e.g., police) want to assess a witness' vulnerability to false memories.…”
Section: Discussionmentioning
confidence: 87%
“…Since previous studies have found a difference in performance on the DRM paradigm between younger and older children (e.g., Brainerd, Holliday, Reyna, Yang, & Toglia, 2010;Brainerd, Reyna, & Zember, 2011), an exploratory repeated measures ANOVA was performed with VALENCE (neutral vs. negative) as within subjects factor and GROUP (high CU group vs. low CU group) and AGE (8/9 years vs. 11/12 years) as between subjects factors. For this analysis, there were 8 8/9-year old children with low CU traits, 6 8/9 year old children with high CU traits, 6 11/12 year old children with low CU traits, and 12 11/12 year old children with high CU traits.…”
Section: Resultsmentioning
confidence: 99%
“…Since previous research has found an age effect in DRM-performance (e.g., Brainerd et al, 2010;Brainerd et al, 2011), the low and high CU children in the present study were divided by age. Results showed that 11/12-year old children with low CU traits recalled significantly more critical lures for the negative word lists compared to the neutral word lists.…”
Section: Discussionmentioning
confidence: 97%
“…well as in recognition (Payne, Ellie, Blackwell, & Neuschatz, 1996; for an overview, see Gallo, 2010). Using the DRM paradigm, many studies have found an increase of false memories from early childhood into adolescence (for overviews, see Brainerd, Reyna, & Ceci, 2008;Brainerd, Reyna, & Zember, 2011). The current study was aimed at examining the processes underlying the DRM illusion in kindergarten and elementary school-aged children.…”
Section: Introductionmentioning
confidence: 99%
“…This development could suggest that children become increasingly efficient at controlling the emergence of false memories. However, many studies on the DRM illusion reported developmental reversals in false memory, meaning higher rates of false memories in older children as compared with younger children (e.g., Brainerd et al, 2008Brainerd et al, , 2011. This increase with age apparently reflects a stronger associative activation of critical items (Wimmer & Howe, 2009) or better gist extraction (Brainerd & Reyna, 2005).…”
Section: Introductionmentioning
confidence: 99%